Review of the book From transnational language policy transfer to local appropriation: The case of the National Bilingual Program in Medellín, Colombia - Norbella Miranda (Asociación Colombiana de Profesores de Ingles, 2017)
Usma Wilches, J. A. (2015). From transnational language policy transfer to local appropriation: The case of the National Bilingual Program in Medellín, Colombia. Deep University Press. 158 pages ISBN-10: 1939755204 ISBN-13: 978-1939755209